African American Social Work Faculty: Overcoming Existing Barriers and Achieving Research Productivity. (March 2018) - Allen, Junior Lloyd; Huggins-Hoyt, Kimberly Y.; Holosko, Michael J.; Briggs, Harold E.
Purpose: This study explored the scholarship experiences of top-ranked African American faculty in schools of social work. Method: Qualitative interviews were conducted with N = 10 top-ranked African American faculty identified as achieving considerable productivity and impact of scholarship. Findings: Four major themes were identified, each of which had 2–3 subcategories. These included (1) mentorship, (2) collaboration, (3) time, and (4) strategic planning. The data revealed that of these identified themes, mentorship was the most prominent, and collaboration, although important, was the least. Implications: The noted experiences and strategies highlighted in this study could be of great utility for those seeking to enhance their scholarly productivity and impact, particularly for (a) junior faculty, (b) African American faculty, and (c) doctoral student researchers and candidates.